Rare Earth Based Magnesium Alloys—A Review on WE Series - Calado, Lénia M.; Carmezim, Maria J.; Montemor, M. Fátima (Frontiers in Materials, 2022)
Magnesium and magnesium alloys have attracted growing attention over the last decades as lightweight materials for a wide range of applications. In particular, WE series magnesium alloys have experienced growing interest over the last years due to their favourable mechanical properties at room and elevated temperatures. In addition, it has been reported that these rare earth-containing alloys possess superior corrosion resistance compared to other commonly used magnesium alloys, such as AZ series. This review aims at providing a concise overview of the research efforts made during recent years regarding the properties of WE series magnesium alloys (e.g. mechanical properties, corrosion behaviour), how these properties can be enhanced by controlling the microstructure of these materials, and the role of specific alloying elements that are used for the WE series. The widespread use of these materials has been limited, mainly due to their susceptibility to corrosion. Thus, in the present review, strong emphasis has been given to recent work studying the corrosion behaviour of the WE series alloys, and to protective strategies that can be employed to mitigate their degradation.